Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/en14082127
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of the Influence of Different Flow Patterns on Power and Reactant Transmission in Tubular-Shaped PEMFC

Abstract: The influence of a tubular structure PEMFC (proton exchange membrane fuel cell) with different flow patterns is investigated in this study. A complete 3D non-isothermal model is constructed for square and circular tubular PEMFCs, and the distribution of oxygen and water concentration in cathode channels, current density, power density and cell net power are studied. To this end, the four arrangements of tubular PEMFC are square chordal (SC), square peripheral (SP), circular chordal (CC) and circular peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Different cross-section shapes, including rectangles, trapezoids, parallelograms, and triangles, have been proposed and studied [45][46][47][48], as shown in Figure 8. As shown in Figure 9, Yang et al [47] found that the molar concentration distribution of oxygen in an M-like channel at the interface between the CL and cathode GDL was more uniform and larger than that in a conventional parallel channel.…”
Section: Optimal Design Of Cross-section and Flow Channel Shapesmentioning
confidence: 99%
See 1 more Smart Citation
“…Different cross-section shapes, including rectangles, trapezoids, parallelograms, and triangles, have been proposed and studied [45][46][47][48], as shown in Figure 8. As shown in Figure 9, Yang et al [47] found that the molar concentration distribution of oxygen in an M-like channel at the interface between the CL and cathode GDL was more uniform and larger than that in a conventional parallel channel.…”
Section: Optimal Design Of Cross-section and Flow Channel Shapesmentioning
confidence: 99%
“…Therefore, more reactants can participate in the electrochemical reaction of the CL, thus improving the performance of PEMFC. Yuan et al [48] comparatively examined the effect of square chordal, square peripheral, circular chordal, and circular peripheral on fuel cell performance. The results showed that the square peripheral with a counter-flow pattern yielded a higher fuel cell performance than the other designs.…”
Section: Optimal Design Of Cross-section and Flow Channel Shapesmentioning
confidence: 99%
“…There has been much discussion over which model is best. A recent study by Yuan et al compared these models using current density data and found that the counterflow model was better for creating the highest power output [12]. However, this study employed more hydrogen, so it can be argued that the co-current model is more efficient, as hydrogen fuel lasts longer when the cell is running.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple serpentine flow models either use co-current flow with gas channels directly above each other or counter-flow with the gas channels running between each other from the cathode to anode sides [11]. Most models seem to do one or the other, and both models appear to be almost as effective as each other [12]. When channels are lined directly above each other, co-current flow has been found to have the highest power output [13].…”
Section: Introductionmentioning
confidence: 99%
“…The traditional flow fields are based on two-dimensional (2D) graphic design and can be classified as lattice [4], parallel [5,6], serpentine [7,8], and interdigital [9,10] structures. The lattice structured bipolar plate has the lowest pressure drop, while the internal fluid velocity is low and the reaction gas has poor directivity, resulting in inconsistent gas distribution uniformity and easy flooding.…”
Section: Introductionmentioning
confidence: 99%